Frontiers in Zoology - Heinze, Juergen; Technau, Ulrich
Frontiers in Zoology is an open access, peer-reviewed online journal publishing high quality research articles and reviews on all aspects of animal life. As a biological discipline, zoology has one of the longest histories. Today it occasionally appears as though, due to the rapid expansion of life sciences, zoology has been replaced by more or less independent sub-disciplines amongst which exchange is often sparse. However, the recent advance of molecular methodology into "classical" fields of biology, and the development of theories that can explain phenomena on different levels of organisation, has led to a re-integration of zoological disciplines promoting a broader than usual approach to zoological questions. Zoology has re-emerged as an integrative discipline encompassing the most diverse aspects of animal life, from the level of the gene to the level of the ecosystem. Frontiers in Zoology is the first open access journal focusing on zoology as a whole. It aims to represent and re-unite the various disciplines that look at animal life from different perspectives and at providing the basis for a comprehensive understanding of zoological phenomena on all levels of analysis. Frontiers in Zoology provides a unique opportunity to publish high quality research and reviews on zoological issues that will be internationally accessible to any reader at no cost. The journal was initiated and is supported by the Deutsche Zoologische Gesellschaft, one of the largest national zoological societies with more than a century-long tradition in promoting high-level zoological research.